Associations of Lipid Levels and Cognition: Findings from the Hispanic Community Health Study/Study of Latinos. (23rd March 2020) - Lamar, Melissa; Durazo-Arvizu, Ramon A.; Rodriguez, Carlos J.; Kaplan, Robert C.; Perera, Marisa J.; Cai, Jianwen; Espinoza Giacinto, Rebeca A.; González, Hector M.; Daviglus, Martha L.
Abstract: Objective: Hispanics/Latinos in the United States are less aware of their cholesterol levels and have a higher burden of associated adverse cardiovascular and cerebrovascular outcomes than non-Latino whites. Investigations of the associations between cholesterol levels and cognition in this population have often occurred within the context of metabolic syndrome and are limited to select lipids despite the fact that triglycerides (TGs) may be more relevant to the health of Hispanics/Latinos. Methods: Baseline data from the Hispanic Community Health Study/Study of Latinos, collected from 2008 to 2011, was used to investigate the associations of lipid levels (i.e., TG, total cholesterol, TC; low-density and high-density lipoprotein cholesterol, LDL-C and HDL-C) with cognition (i.e., learning, memory, verbal fluency, and digit symbol substitution, DSS), adjusting for relevant confounders. Results: In 7413 participants ages 45 to 74 years from Central American, Cuban, Dominican, Mexican, Puerto Rican, and South American backgrounds, separate, fully adjusted linear regression models revealed that TG levels were inversely associated with DSS performance; however, this relationship was no longer significant once additional cardiovascular disease risk factors were added to the model ( p = .06). TC and LDL-C levels (separately) were positively associated with learning and verbal fluency regardless of adjustments ( p -values < .05). Separate analyses investigating the effect modification by background and sex revealed a particularly robust association between TC levels and DSS performance for Puerto Ricans and Central Americans (albeit in opposite directions) and an inverse relationship between TG levels and DSS performance for women ( p -values < .02). Conclusions: It is important to consider individual lipid levels and demographic characteristics when investigating associations between cholesterol levels and cognition in Hispanics/Latinos.